The effect of defects in tin-based perovskites and their photovoltaic devices. (November 2021) - Cao, H.; Zhang, Z.; Zhang, M.; Gu, A.; Yu, H.; Ban, H.; Sun, Q.; Shen, Y.; Zhang, X.-L.; Zhu, J.; Wang, M.
Abstract: Tin-based perovskite solar cells have exhibited great potential for their small bandgap, high carrier mobility, and non-toxic property. With an ever-increasing interest in putting on these lead-free perovskites, the oxidation of Sn(Ⅱ) to Sn(Ⅳ) has been revealed as one of the most crucial issues on their photovoltaic performance. Herein, the sources and impact of Sn(Ⅱ) oxidation and the correlated defects have been reviewed along with the suppression approaches. Compared to these defects in lead-based perovskites, the Sn vacancy dominants tin-based perovskite lattice due to their low formation energy. The essentially easy Sn(Ⅱ) oxidation can be attributed to the intrinsically low standard redox potential of Sn(Ⅱ)/Sn(Ⅳ) couple (0.15 V vs. SHE). Consequently, tin oxidation and its corresponding defective behavior seriously affect the device photovoltaic performance including output photovoltage and power conversion efficiency. We summarize these methods to suppress tin oxidation, such as tin halide compensation, reducing agents, composition and morphology optimization, and encapsulation. We further propose the prospective possible explorations for further restraining the tin oxidation process to improve the performances of tin-based perovskite solar cells. Graphical abstract: Image 1 Highlights: Defect is unavoidable in solution-processed Tin-based perovskite compounds. Defect plays an important role in the photovoltaic parameters and stability of Tin-based perovskites and their devices. This article summarizes up-to-date methods to suppress tin oxidation and other instability issues in Tin-based perovskites